BALALARDA KOORDINACIYALÍQ QÁBILETLERDI RAWAJLANDÍRÍWDA GIMNASTIKALÍQ ELEMENTLERDEN PAYDALANÍW ÓZGESHELIKLERI (5-6 JASAR BALALAR MÍSALÍNDA) - Allambergenova, R.D. (FAN va JAMIYAT, 2024)
this article describes the features of using gymnastic equipment in the development of coordination skills in children using the example of children 5-6 years old.